Composite butyronitrile glove as well as preparation method and application thereof
By adopting a double-layer structure design in medical nitrile gloves, combining materials such as wild rice extract, bamboo fibers of lignin nanoparticles and nanosilicon dioxide, the problem that traditional gloves cannot take into account both antibacterial, wear-resistant and anti-slip properties is solved, and a more efficient medical protection effect is achieved.
Patent Information
- Application Number
- CN202510097233.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2045-01-22
AI Technical Summary
Existing medical nitrile gloves are prone to bacterial contamination during use, and the addition of antibacterial agents is poorly compatible with nitrile latex, which leads to the impact of the wear resistance and anti-slip properties of the gloves, and cannot take into account both antibacterial and mechanical properties.
The composite nitrile glove design is designed with a double-layer structure. The antibacterial lining layer contains wild rice extract and bamboo fibers with lignin nanoparticles attached to the surface. The anti-slip wear-resistant layer contains a mixture of nanosilicon dioxide and carbon black, and the chloroether rubber-coated carbon fibers. Through the synergy of each raw material, the antibacterial, wear-resistant and anti-slip properties of the gloves are improved.
It achieves good surface wear resistance and anti-slip performance of gloves, and also has excellent antibacterial properties, effectively protecting the hand health of medical workers.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical protection, and in particular to a composite nitrile glove and a preparation method and application thereof. Background Art
[0002] Medical gloves are indispensable protective equipment in medical operations. Their main function is to prevent cross-infection between medical staff and patients. Nitrile rubber has become a common material for medical gloves due to its good elasticity, wear resistance and chemical stability. However, traditional medical nitrile gloves do not have antibacterial properties. During use, the gloves are easily contaminated with various bacteria, such as Staphylococcus aureus and Escherichia coli. These bacteria may multiply on the surface of the gloves, increasing the risk of cross-infection. They may also erode the hands of medical workers through the gloves, endangering the personal health of medical workers. Therefore, the development of medical nitrile gloves with antibacterial properties is of great clinical significance.
[0003] At present, it is reported that adding antibacterial agents during the preparation of gloves can improve the antibacterial effect of nitrile gloves. However, the antibacterial agent has poor compatibility with nitrile latex, and a large amount of antibacterial agent needs to be added, which leads to a significant impact on the wear resistance and anti-slip properties of nitrile rubber gloves, and it is impossible to take into account the antibacterial and mechanical properties of the gloves.
[0004] Based on this, the development of a medical nitrile glove with good wear resistance, good anti-slip performance and good antibacterial properties is of great significance to the development of medical materials. Summary of the invention
[0005] In view of the problem that the existing medical antibacterial nitrile gloves cannot take into account the wear resistance, anti-skid performance and antibacterial performance, the present invention provides a composite nitrile glove and its preparation method and application. The composite nitrile glove includes an antibacterial lining layer and an anti-skid wear-resistant layer, wherein the antibacterial lining layer includes the following raw material components: antibacterial material, nitrile rubber, stabilizer, cross-linking agent, accelerator and vulcanizing agent; wherein the antibacterial material includes wild rice stem extract and bamboo fiber with lignin nanoparticles attached to the surface; the anti-skid wear-resistant layer includes the following raw material components: wear-resistant filler, nitrile rubber, high cis polybutadiene rubber, chloroether rubber coated carbon fiber, stabilizer, cross-linking agent, accelerator and vulcanizing agent. The present invention utilizes the synergistic effect of various raw materials to prepare a composite nitrile glove with good surface wear resistance and anti-skid performance, and excellent antibacterial performance, which can effectively protect the hand health of medical workers.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: A first aspect of the present invention provides a composite nitrile glove, comprising an antibacterial lining layer and an anti-slip and wear-resistant layer, wherein the antibacterial lining layer comprises the following raw material components in parts by weight: 5-10 parts of antibacterial material, 60-70 parts of nitrile rubber, 1-5 parts of stabilizer, 1-5 parts of accelerator and 1-5 parts of vulcanizer; wherein the antibacterial material comprises wild rice stem extract and bamboo fiber with lignin nanoparticles attached to the surface; The anti-skid and wear-resistant layer comprises the following raw material components in parts by mass: 10-20 parts of wear-resistant filler, 40-60 parts of nitrile rubber, 5-10 parts of high-cis polybutadiene rubber, 5-15 parts of chloroether rubber-coated carbon fiber, 1-5 parts of stabilizer, 1-5 parts of accelerator and 1-5 parts of vulcanizer; wherein the wear-resistant filler is a mixture of nano-silicon dioxide and carbon black.
[0007] The invention provides a composite nitrile glove with a double-layer structure, wherein the inner material thereof adopts an antibacterial nitrile rubber composite material, and the outer surface adopts a wear-resistant and non-slip nitrile rubber composite material. In the antibacterial inner lining layer, a wild rice extract and bamboo fiber with lignin nanoparticles attached to the surface are added as antibacterial materials. The wild rice extract is rich in tricin and phenolic acid substances, and tricin has good antioxidant and anti-inflammatory effects; while the phenolic acid substances have good antibacterial effects, interfere with the activity of key enzymes in the synthesis process of bacterial cell walls, so that the bacterial cell walls cannot be assembled normally, and cause bacterial cells to be inactivated under the action of osmotic pressure, thereby achieving the purpose of antibacterial. The wild rice extract can reduce the decomposition of water retention factors, increase the water content of the skin, repair the skin barrier, and avoid sensitive redness and swelling of the skin caused by the action of bacteria. The bamboo fiber with lignin nanoparticles attached to the surface can serve as a physical barrier, and the lignin nanoparticles on the surface of the bamboo fiber can form a layer of physical barrier. These nanoparticles can cover the surface of the bamboo fiber, making it difficult for bacteria to directly contact and adhere to the bamboo fiber, thereby reducing the chance of bacteria colonizing on the fiber surface. Moreover, lignin itself has a variety of active functional groups, such as phenolic hydroxyl groups. These active groups can be slowly released from the nanoparticles and enter the surrounding environment to contact bacteria. Phenolic hydroxyl groups have good antibacterial properties and can destroy the bacterial cell membrane structure. The cell membrane is a key structure for bacteria to maintain the stability of the intracellular environment and exchange substances. When active ingredients such as phenolic hydroxyl groups come into contact with the cell membrane, the permeability of the cell membrane will change, allowing important substances in the bacterial cells to leak, thereby affecting the normal metabolism and physiological functions of the bacteria, and ultimately leading to the death of the bacteria, achieving the purpose of antibacterial.
[0008] Most of the double bonds in the molecular chain of high cis polybutadiene rubber are cis structures, which makes the molecular chain have high regularity and can be closely arranged. The closely arranged molecular chains give the rubber high elasticity and tensile strength. When subjected to external forces, the molecular chains can quickly stretch and recover, thereby effectively buffering and dispersing pressure, making the gloves have good elasticity and anti-slip properties. Nano-silica and carbon black in wear-resistant fillers can interact with high cis polybutadiene rubber and nitrile rubber, which can not only enhance the hardness and rigidity of rubber materials, but also adsorb rubber molecular chains to prevent molecular chains from slipping during friction, thereby improving the wear resistance of rubber materials. The addition of chloroether rubber coated carbon fibers can form a microscopic rough surface. This microscopic rough structure can increase the contact area and friction between the contacting object and increase the anti-slip performance. Carbon fibers can effectively disperse these stresses with their high strength, avoid stress concentration at a certain point and cause material damage, and improve the overall wear resistance of the material.
[0009] Preferably, the mass ratio of the wild rice stem extract in the antibacterial material to the bamboo fiber with lignin nanoparticles attached to the surface is 1:5-1:8.
[0010] Preferably, the thickness of the antibacterial lining layer is 100-200 μm.
[0011] Preferably, the anti-slip and wear-resistant layer has a thickness of 150-250 μm.
[0012] Preferably, the method for preparing the wild rice stem extract comprises the following steps: crushing the wild rice stem and performing vacuum freeze drying to obtain wild rice stem powder; dispersing the wild rice stem powder in a low-boiling point organic mixed solvent, performing ultrasound, performing solid-liquid separation, concentrating the filtrate, purifying, and drying to obtain the wild rice stem extract.
[0013] Further preferably, the low boiling point organic mixed solvent is ethyl acetate and ethanol in a volume ratio of 1:1-1:3.
[0014] More preferably, the ultrasonic temperature is 40-50° C., and the ultrasonic time is 30-50 min.
[0015] More preferably, purification is performed by column chromatography, and the eluent is dichloromethane and petroleum ether in a volume ratio of 1:2-1:2.5.
[0016] More preferably, the drying temperature is 70-80° C., and the drying time is 6-10 h.
[0017] Preferably, the method for preparing the bamboo fiber with lignin nanoparticles attached to the surface comprises the following steps: S1, dissolving lignin in a good solvent to obtain a lignin solution; slowly adding the lignin solution to an anti-solvent, mixing evenly, filtering, washing, and drying to obtain lignin nanoparticles; S2, dispersing the bamboo fibers in an alkaline solution for activation treatment to obtain pretreated bamboo fibers; S3, dispersing the lignin nanoparticles in an alcohol solution of a coupling agent, mixing evenly, adding the pretreated bamboo fiber, performing an attachment reaction at 60-75° C., filtering, washing, and drying to obtain the bamboo fiber with lignin nanoparticles attached to the surface.
[0018] Further preferably, in S1, the good solvent is dimethyl sulfoxide or tetrahydrofuran; and the anti-solvent is water.
[0019] Further preferably, in S1, the mass volume ratio of the lignin to the good solvent is 1 g:2 mL-1 g:4 mL.
[0020] Further preferably, in S1, the rotation speed of the high-speed stirring is 1500 rpm-1800 rpm, and the time of the high-speed stirring is 10-15 min.
[0021] Further preferably, in S1, the drying temperature is 80-90° C., and the drying time is 3-5 h.
[0022] Further preferably, in S2, the mass volume ratio of the bamboo fiber to the alkaline solution is 1g:4mL-1g:6mL.
[0023] Further preferably, in S2, the alkaline solution is a sodium hydroxide solution with a concentration of 0.5 mol / L-1 mol / L.
[0024] Further preferably, in S2, the temperature of the activation treatment is 50-60°C, and the time of the activation treatment is 20-30 minutes.
[0025] Further preferably, in S3, the mass volume ratio of the lignin nanoparticles to the alcohol solution of the coupling agent is 1g:5mL-1g:10mL; wherein the mass percentage of the coupling agent in the alcohol solution of the coupling agent is 50%-60%.
[0026] Further preferably, in S3, the attachment reaction time is 2-5 hours.
[0027] Preferably, the preparation method of the epichlorohydrin rubber coated carbon fiber comprises the following steps: dissolving epichlorohydrin rubber in an organic solvent to obtain an epichlorohydrin rubber solution; immersing short carbon fibers in the epichlorohydrin rubber solution, separating the solid from the liquid, and drying to obtain epichlorohydrin rubber coated carbon fibers.
[0028] Further preferably, the mass volume ratio of the chloroether rubber to the organic solvent is 1g:3mL-1g:5mL.
[0029] More preferably, the organic solvent is dichloromethane.
[0030] Further preferably, the length of the short carbon fibers is 0.5 mm-1.5 mm.
[0031] Further preferably, the mass ratio of the short carbon fiber to the epichlorohydrin rubber is 1:1-1:2.
[0032] More preferably, the drying temperature is 110-130° C., and the drying time is 30-50 min.
[0033] Preferably, the wear-resistant filler is nano-silicon dioxide and carbon black in a mass ratio of 1:1-1:2.
[0034] Preferably, the stabilizer is 2,6-di-tert-butyl-p-cresol.
[0035] Preferably, the accelerator is accelerator DM.
[0036] Preferably, the vulcanizing agent is dicumyl peroxide or benzoyl peroxide.
[0037] The second aspect of the present invention provides a method for preparing the composite nitrile gloves, comprising the following steps: Step 1: weigh the raw materials of each component of the antibacterial lining layer according to the designed ratio, mix them evenly, and vulcanize them to obtain the antibacterial lining layer rubber material; Weigh the raw materials of various components of the anti-skid and wear-resistant layer according to the designed ratio, mix them evenly, and vulcanize them to obtain the anti-skid and wear-resistant layer rubber material; Step 2: stacking the antibacterial lining rubber material and the anti-skid and wear-resistant layer rubber material, and compression molding them to obtain composite nitrile gloves.
[0038] Preferably, in step 1, the vulcanization temperature is 160-180° C., and the vulcanization time is 16-22 hours.
[0039] The third aspect of the present invention provides the use of the composite nitrile gloves in the field of medical protection.
[0040] In summary, the present invention utilizes the synergistic effect of various raw material components to obtain a composite nitrile glove with good surface wear resistance and anti-slip performance, and also has antibacterial performance. The technical solution of the present invention effectively solves the problem that the existing medical antibacterial nitrile gloves cannot take into account the wear resistance, anti-slip performance and antibacterial performance, effectively protects the hand health of medical workers, and provides a new idea for the research and development of medical protective materials. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1 This embodiment provides a composite nitrile glove and a preparation method thereof, which specifically includes the following contents: The composite nitrile gloves include an antibacterial lining layer and an anti-slip and wear-resistant layer, wherein the antibacterial lining layer includes the following raw material components in mass fractions: 8 parts of antibacterial material, 65 parts of nitrile rubber, 3 parts of 2,6-di-tert-butyl-p-cresol, 3 parts of accelerator DM and 3 parts of diisopropylbenzene peroxide; wherein the antibacterial material includes wild rice stem extract and bamboo fiber with lignin nanoparticles attached to the surface in a mass ratio of 1:6; The anti-skid and wear-resistant layer includes the following raw material components in parts by mass: 15 parts of wear-resistant filler, 50 parts of nitrile rubber, 8 parts of high-cis polybutadiene rubber, 10 parts of chloroether rubber-coated carbon fiber, 3 parts of 2,6-di-tert-butyl-p-cresol, 3 parts of accelerator DM and 3 parts of diisopropylbenzene peroxide; wherein the wear-resistant filler is a mixture of nano-silica and carbon black in a mass ratio of 1:1.5.
[0043] The preparation method of the composite nitrile gloves comprises the following steps: Step 1: weigh the raw materials of each component of the antibacterial lining layer according to the designed ratio, mix them evenly, vulcanize them at 170° C. for 18 hours, and cool them to room temperature to obtain the antibacterial lining layer rubber material; Weigh the raw materials of the anti-skid and wear-resistant layer according to the designed ratio, mix them evenly, vulcanize them at 175°C for 20 hours, and cool them to room temperature to obtain the anti-skid and wear-resistant layer rubber material; Step 2: stack the antibacterial lining rubber material and the anti-skid and wear-resistant layer rubber material in order from inside to outside, wherein the thickness of the antibacterial lining layer is 150 μm; the thickness of the anti-skid and wear-resistant layer is 200 μm, and perform compression molding to obtain a composite nitrile glove.
[0044] The preparation method of the wild rice stem extract comprises the following steps: crushing 1000g of wild rice stem and performing vacuum freeze drying to obtain wild rice stem powder; dispersing the wild rice stem powder in 2000mL of ethyl acetate and ethanol in a volume ratio of 1:1, performing ultrasonic treatment at 45°C for 40min, performing solid-liquid separation, concentrating the filtrate, and performing purification treatment by column chromatography. The eluent is dichloromethane and petroleum ether in a volume ratio of 1:2, removing the solvent, and drying at 75°C for 8h to obtain the wild rice stem extract.
[0045] The method for preparing the bamboo fiber with lignin nanoparticles attached to the surface comprises the following steps: S1. Dissolve 500 g of lignin in 1500 mL of dimethyl sulfoxide to obtain a lignin solution; slowly add the lignin solution into water while stirring at a speed of 1600 rpm for 12 min, filter, wash with water 3 times, and dry at 85° C. for 4 h to obtain lignin nanoparticles; S2, dispersing 500g of bamboo fiber in a sodium hydroxide solution with a concentration of 0.6mol / L, and performing activation treatment at 55°C for 25min to obtain pretreated bamboo fiber; S3, dispersing the lignin nanoparticles in 3000 mL of an alcohol solution of a coupling agent, mixing evenly, adding the pretreated bamboo fiber, performing an attachment reaction at 75° C. for 3 h, filtering, washing with ethanol for 3 times, and drying to obtain the bamboo fiber with lignin nanoparticles attached to the surface.
[0046] The preparation method of the chloroprene rubber coated carbon fiber comprises the following steps: dissolving 500 g of chloroprene rubber in 2000 mL of dichloromethane to obtain a chloroprene rubber solution; immersing short carbon fibers with a length of 1 mm in the chloroprene rubber solution, standing for 12 hours, separating the solid from the liquid, and drying at 120° C. for 40 minutes to obtain the chloroprene rubber coated carbon fiber.
[0047] Example 2 This embodiment provides a composite nitrile glove and a preparation method thereof, which specifically includes the following contents: The composite nitrile gloves include an antibacterial lining layer and an anti-slip wear-resistant layer, wherein the antibacterial lining layer includes the following raw material components in mass fractions: 5 parts of antibacterial material, 70 parts of nitrile rubber, 3 parts of 2,6-di-tert-butyl-p-cresol, 3 parts of accelerator DM and 3 parts of diisopropylbenzene peroxide; wherein the antibacterial material includes wild rice stem extract and bamboo fiber with lignin nanoparticles attached to the surface in a mass ratio of 1:8; The anti-skid and wear-resistant layer includes the following raw material components in parts by mass: 15 parts of wear-resistant filler, 50 parts of nitrile rubber, 8 parts of high-cis polybutadiene rubber, 10 parts of chloroether rubber-coated carbon fiber, 3 parts of 2,6-di-tert-butyl-p-cresol, 3 parts of accelerator DM and 3 parts of diisopropylbenzene peroxide; wherein the wear-resistant filler is a mixture of nano-silica and carbon black in a mass ratio of 1:2.
[0048] The preparation method of the composite nitrile gloves comprises the following steps: Step 1: weigh the raw materials of each component of the antibacterial lining layer according to the designed ratio, mix them evenly, vulcanize them at 170° C. for 18 hours, and cool them to room temperature to obtain the antibacterial lining layer rubber material; Weigh the raw materials of the anti-skid and wear-resistant layer according to the designed ratio, mix them evenly, vulcanize them at 175°C for 20 hours, and cool them to room temperature to obtain the anti-skid and wear-resistant layer rubber material; Step 2: stack the antibacterial lining rubber material and the anti-skid and wear-resistant layer rubber material in order from inside to outside, wherein the thickness of the antibacterial lining layer is 150 μm; the thickness of the anti-skid and wear-resistant layer is 200 μm, and perform compression molding to obtain a composite nitrile glove.
[0049] The preparation method of the wild rice stem extract comprises the following steps: crushing 1000g of wild rice stem and performing vacuum freeze drying to obtain wild rice stem powder; dispersing the wild rice stem powder in 2000mL of ethyl acetate and ethanol in a volume ratio of 1:1, performing ultrasonic treatment at 45°C for 40min, performing solid-liquid separation, concentrating the filtrate, and performing purification treatment by column chromatography. The eluent is dichloromethane and petroleum ether in a volume ratio of 1:2, removing the solvent, and drying at 75°C for 8h to obtain the wild rice stem extract.
[0050] The method for preparing the bamboo fiber with lignin nanoparticles attached to the surface comprises the following steps: S1. Dissolve 500 g of lignin in 1500 mL of dimethyl sulfoxide to obtain a lignin solution; slowly add the lignin solution into water while stirring at a speed of 1600 rpm for 12 min, filter, wash with water 3 times, and dry at 85° C. for 4 h to obtain lignin nanoparticles; S2, dispersing 500g of bamboo fiber in a sodium hydroxide solution with a concentration of 0.6mol / L, and performing activation treatment at 55°C for 25min to obtain pretreated bamboo fiber; S3, dispersing the lignin nanoparticles in 3000 mL of an alcohol solution of a coupling agent, mixing evenly, adding the pretreated bamboo fiber, performing an attachment reaction at 75° C. for 3 h, filtering, washing with ethanol for 3 times, and drying to obtain the bamboo fiber with lignin nanoparticles attached to the surface.
[0051] The preparation method of the chloroprene rubber coated carbon fiber comprises the following steps: dissolving 500 g of chloroprene rubber in 2000 mL of dichloromethane to obtain a chloroprene rubber solution; immersing short carbon fibers with a length of 1 mm in the chloroprene rubber solution, standing for 12 hours, separating the solid from the liquid, and drying at 120° C. for 40 minutes to obtain the chloroprene rubber coated carbon fiber.
[0052] Example 3 This embodiment provides a composite nitrile glove and a preparation method thereof, which specifically includes the following contents: The composite nitrile gloves include an antibacterial lining layer and an anti-slip wear-resistant layer, wherein the antibacterial lining layer includes the following raw material components by weight: 10 parts of antibacterial material, 60 parts of nitrile rubber, 5 parts of 2,6-di-tert-butyl-p-cresol, 3 parts of accelerator DM and 4 parts of diisopropylbenzene peroxide; wherein the antibacterial material includes wild rice stem extract and bamboo fiber with lignin nanoparticles attached to the surface in a mass ratio of 1:5; The anti-skid and wear-resistant layer includes the following raw material components in parts by mass: 15 parts of wear-resistant filler, 50 parts of nitrile rubber, 8 parts of high-cis polybutadiene rubber, 10 parts of chloroether rubber-coated carbon fiber, 3 parts of 2,6-di-tert-butyl-p-cresol, 3 parts of accelerator DM and 3 parts of diisopropylbenzene peroxide; wherein the wear-resistant filler is a mixture of nano-silica and carbon black in a mass ratio of 1:1.
[0053] The preparation method of the composite nitrile gloves comprises the following steps: Step 1: weigh the raw materials of each component of the antibacterial lining layer according to the designed ratio, mix them evenly, vulcanize them at 170° C. for 18 hours, and cool them to room temperature to obtain the antibacterial lining layer rubber material; Weigh the raw materials of the anti-skid and wear-resistant layer according to the designed ratio, mix them evenly, vulcanize them at 175°C for 20 hours, and cool them to room temperature to obtain the anti-skid and wear-resistant layer rubber material; Step 2: stack the antibacterial lining rubber material and the anti-skid and wear-resistant layer rubber material in order from inside to outside, wherein the thickness of the antibacterial lining layer is 150 μm; the thickness of the anti-skid and wear-resistant layer is 200 μm, and perform compression molding to obtain a composite nitrile glove.
[0054] The preparation method of the wild rice stem extract comprises the following steps: crushing 1000g of wild rice stem and performing vacuum freeze drying to obtain wild rice stem powder; dispersing the wild rice stem powder in 2000mL of ethyl acetate and ethanol in a volume ratio of 1:1, performing ultrasonic treatment at 45°C for 40min, performing solid-liquid separation, concentrating the filtrate, and performing purification treatment by column chromatography. The eluent is dichloromethane and petroleum ether in a volume ratio of 1:2, removing the solvent, and drying at 75°C for 8h to obtain the wild rice stem extract.
[0055] The method for preparing the bamboo fiber with lignin nanoparticles attached to the surface comprises the following steps: S1. Dissolve 500 g of lignin in 1500 mL of dimethyl sulfoxide to obtain a lignin solution; slowly add the lignin solution into water while stirring at a speed of 1600 rpm for 12 min, filter, wash with water 3 times, and dry at 85° C. for 4 h to obtain lignin nanoparticles; S2, dispersing 500g of bamboo fiber in a sodium hydroxide solution with a concentration of 0.6mol / L, and performing activation treatment at 55°C for 25min to obtain pretreated bamboo fiber; S3, dispersing the lignin nanoparticles in 3000 mL of an alcohol solution of a coupling agent, mixing evenly, adding the pretreated bamboo fiber, performing an attachment reaction at 75° C. for 3 h, filtering, washing with ethanol for 3 times, and drying to obtain the bamboo fiber with lignin nanoparticles attached to the surface.
[0056] The preparation method of the chloroprene rubber coated carbon fiber comprises the following steps: dissolving 500 g of chloroprene rubber in 2000 mL of dichloromethane to obtain a chloroprene rubber solution; immersing short carbon fibers with a length of 1 mm in the chloroprene rubber solution, standing for 12 hours, separating the solid from the liquid, and drying at 120° C. for 40 minutes to obtain the chloroprene rubber coated carbon fiber.
[0057] Comparative Example 1 This comparative example provides a composite nitrile glove, which is different from Example 1 in that the antibacterial material is bamboo fiber with lignin nanoparticles attached to the surface, and other components and processes remain unchanged and will not be described again here.
[0058] Comparative Example 2 This comparative example provides a composite nitrile glove, which is different from Example 1 in that the wild rice stem extract is replaced with an equal amount of konjac extract, and other ingredients and processes remain unchanged, which will not be described again.
[0059] The preparation method of the konjac extract comprises the following steps: crushing 1000g of konjac and performing vacuum freeze drying to obtain konjac flour; dispersing the konjac flour in 2000mL of ethyl acetate and ethanol in a volume ratio of 1:1, performing ultrasonic treatment at 45°C for 40min, performing solid-liquid separation, concentrating the filtrate, and performing purification treatment by column chromatography. The eluent is dichloromethane and petroleum ether in a volume ratio of 1:2, removing the solvent, and drying at 75°C for 8h to obtain the konjac extract.
[0060] Comparative Example 3 This comparative example provides a composite nitrile glove, which differs from Example 1 in that high cis polybutadiene rubber is replaced with an equal amount of ethylene propylene diene monomer rubber, and other components and processes remain unchanged, which will not be described again.
[0061] Comparative Example 4 This comparative example provides a composite nitrile glove, which differs from Example 1 in that the chloroether rubber-coated carbon fiber is replaced with an equal amount of carbon fiber, and other components and processes remain unchanged, which will not be described again here.
[0062] In order to further reflect the technical effect of the present invention, the present invention conducted the following tests on the layered rubber materials obtained in Examples 1-3 and Comparative Examples 1-4: (1) referring to GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber" standard, the tensile strength and elongation at break of the gloves were tested using a universal material testing machine; (2) referring to ASTM F1677-2016, the anti-slip performance was tested using a portable anti-slip tester; (3) referring to GB / T 1689-2014, the wear resistance was tested; (4) referring to GB 15979-2002, the antibacterial performance of the gloves was tested, and the test results are shown in Table 1.
[0063] Table 1 Performance test results of various layered rubber materials
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite nitrile glove, characterized in that: The composite nitrile gloves include an antibacterial lining layer and an anti-slip wear-resistant layer, wherein the antibacterial lining layer includes the following raw material components in parts by weight: 5-10 parts of antibacterial material, 60-70 parts of nitrile rubber, 1-5 parts of stabilizer, 1-5 parts of accelerator and 1-5 parts of vulcanizer; wherein the antibacterial material includes wild rice stem extract and bamboo fiber with lignin nanoparticles attached to the surface; The anti-skid and wear-resistant layer comprises the following raw material components in parts by mass: 10-20 parts of wear-resistant filler, 40-60 parts of nitrile rubber, 5-10 parts of high-cis polybutadiene rubber, 5-15 parts of chloroether rubber-coated carbon fiber, 1-5 parts of stabilizer, 1-5 parts of accelerator and 1-5 parts of vulcanizer; wherein the wear-resistant filler is a mixture of nano-silicon dioxide and carbon black.
2. The composite nitrile glove according to claim 1, characterized in that: The mass ratio of the wild rice stem extract in the antibacterial material to the bamboo fiber with lignin nanoparticles attached to the surface is 1:5-1:8; and / or The thickness of the antibacterial lining layer is 100-200 μm; and / or The thickness of the anti-skid and wear-resistant layer is 150-250 μm.
3. The composite nitrile glove according to claim 1 or 2, characterized in that: The preparation method of the wild rice stem extract comprises the following steps: crushing the wild rice stem and performing vacuum freeze drying to obtain wild rice stem powder; dispersing the wild rice stem powder in a low-boiling point organic mixed solvent, performing ultrasound, performing solid-liquid separation, concentrating the filtrate, purifying, and drying to obtain the wild rice stem extract.
4. The composite nitrile glove according to claim 3, characterized in that: The low boiling point organic mixed solvent is ethyl acetate and ethanol in a volume ratio of 1:1-1:3; and / or The ultrasonic temperature is 40-50°C and the ultrasonic time is 30-50min; and / or The product is purified by column chromatography, and the eluent is dichloromethane and petroleum ether in a volume ratio of 1:2-1:2.
5.
5. The composite nitrile glove according to claim 1 or 2, characterized in that: The method for preparing the bamboo fiber with lignin nanoparticles attached to the surface comprises the following steps: S1, dissolving lignin in a good solvent to obtain a lignin solution; slowly adding the lignin solution to an anti-solvent, mixing evenly, filtering, washing, and drying to obtain lignin nanoparticles; S2, dispersing the bamboo fibers in an alkaline solution for activation treatment to obtain pretreated bamboo fibers; S3, dispersing the lignin nanoparticles in an alcohol solution of a coupling agent, mixing evenly, adding the pretreated bamboo fiber, performing an attachment reaction at 60-75° C., filtering, washing, and drying to obtain the bamboo fiber with lignin nanoparticles attached to the surface.
6. The composite nitrile glove according to claim 5, characterized in that: In S1, the good solvent is dimethyl sulfoxide or tetrahydrofuran; the anti-solvent is water; and / or In S1, the mass volume ratio of the lignin to the good solvent is 1g:2mL-1g:4mL; and / or In S2, the mass volume ratio of the bamboo fiber to the alkaline solution is 1g:4mL-1g:6mL; and / or In S2, the temperature of the activation treatment is 50-60°C, and the time of the activation treatment is 20-30 minutes.
7. The composite nitrile glove according to claim 5, characterized in that: In S3, the mass volume ratio of the lignin nanoparticles to the alcohol solution of the coupling agent is 1g:5mL-1g:10mL; wherein the mass percentage of the coupling agent in the alcohol solution of the coupling agent is 50%-60%; and / or In S3, the attachment reaction time is 2-5 hours.
8. The composite nitrile glove according to claim 1, characterized in that: The preparation method of the chloroprene rubber coated carbon fiber comprises the following steps: dissolving chloroprene rubber in an organic solvent to obtain a chloroprene rubber solution; immersing short carbon fibers in the chloroprene rubber solution, separating the solid from the liquid, and drying to obtain the chloroprene rubber coated carbon fiber; and / or The wear-resistant filler is nano silicon dioxide and carbon black in a mass ratio of 1:1-1:
2.
9. The method for preparing the composite nitrile gloves according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: weigh the raw materials of each component of the antibacterial lining layer according to the designed ratio, mix them evenly, and vulcanize them to obtain the antibacterial lining layer rubber material; Weigh the raw materials of various components of the anti-skid and wear-resistant layer according to the designed ratio, mix them evenly, and vulcanize them to obtain the anti-skid and wear-resistant layer rubber material; Step 2: stacking the antibacterial lining rubber material and the anti-skid and wear-resistant layer rubber material, and compression molding them to obtain composite nitrile gloves.
10. Use of the composite nitrile gloves according to any one of claims 1 to 8 in the field of medical protection.
Citation Information
Patent Citations
Preparation method of weather-resistant composite for bicycle handle
CN105038227A
High-wear-resistance composite rubber material and preparation method thereof
CN115873319A
Lignin nanoparticles as well as preparation method and application thereof
CN115926206A
Modified plant fiber composite material for hard tissue repair and preparation method thereof
CN118236555A
Antiskid protective glove and preparation method thereof
CN118322445A